Rakku's story : structures of ill-health and the source of change - Zurbrigg, Sheila (Published by George Joseph on behalf of the author ; Available from Centre for Social Action, 1984)
Causes of rural ill-health in India; based on the authorʼs experiences in Tamil Nadu.